Comparison of Dose Distribution in Proton and Gamma Radiation for Cervical Cancer Using Monte Carlo Simulation - Urfa, Gusti Atika; Kartika, Listiana; Fitrianti, Intan; Seftina, Rahmi; Rachman, Rezky Rachmadhany; Wianto, Totok; Sudarningsih, Sudarningsih; Suarso, Eka (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
Precision in radiation dose delivery is critical in cervical cancer treatment to ensure effective tumor control while minimizing damage to surrounding healthy tissues. Given the increasing adoption of advanced radiation therapies, comparative studies on dose distribution between different modalities are essential for evidence-based treatment planning. This study aims to compare the dose absorption in cervical cancer treatment using proton and gamma radiation through Monte Carlo simulation modeling. A Monte Carlo simulation was conducted using the Particle and Heavy Ion Transport code System (PHITS). Proton beams with an energy of 120 MeV and gamma rays at 30 MeV were applied from the anteroposterior (AP) direction using a pencil beam configuration (1 mm × 1 mm). Anatomical data were obtained from Digital Imaging and Communications in Medicine (DICOM) files sourced from RSUD Ulin Banjarmasin. Dose distribution was assessed in the target region and organs at risk (OAR). The results showed that proton therapy delivered a higher absorbed dose to the cervical target area (34.5 ± 1.5 MeV) than gamma radiation (16.7 ± 2.3 MeV). While both conformed to ICRU Report No. 78, gamma radiation resulted in higher doses to nearby organs such as the rectum and bladder, indicating a greater risk of radiation-induced side effects. Proton therapy offers more targeted dose delivery with reduced exposure to surrounding organs, making it a potentially safer and more effective modality for cervical cancer treatment. These findings underscore the importance of modality selection in optimizing therapeutic outcomes and minimizing complications in radiotherapy.